Fungi in dialysis water and dialysate: occurrence, susceptibility to antifungal agents and biofilm production capacity - Laís Anversa; Bruna Rossini Lara; Caroline Demai Romani; Erika Kushikawa Saeki; Gabriel Antonio Nogueira Nascentes; Lucas Xavier Bonfietti; Márcia de Souza Carvalho Melhem; Luciana da Silva Ruiz; Carlos Henrique Camargo; Virgínia Bodelão Richini Pereira (IWA Publishing, 2021)
The aim of this study was to investigate the occurrence of fungi in dialysis water and dialysate, in addition to evaluating the susceptibility to antifungals and the biofilm production capacity of isolated microorganisms. The samples were collected in three hemodialysis units in Bauru (Brazil), every 15 days (July 2017-June 2018) at post-reverse osmosis, reuse, and dialysate points. The fungi were isolated by spread plate on Sabouraud dextrose agar. Filamentous fungi were phenotypically identified and yeasts were subjected to molecular evaluation of the ITS region. Susceptibility test to antifungals was carried out by the broth microdilution method and biofilm production capacity was evaluated in microtiter plates using crystal violet staining. Fungi were isolated in 52/216 (24.1%) samples, with an average count of 16.3 (10-40) CFU/mL. Overall, 61 microorganisms were identified, with 54 (88.5%) filamentous fungi and 7 (11.5%) yeasts. The main genera included were Penicillium, Cladosporium, Scedosporium, Rhinocladiella, Fusarium, and Emmonsia. Most isolates showed high values of minimum inhibitory concentration for 5-flucytosine and fluconazole and 35/45 (77.8%) isolates were classified as strong producers of biofilm. In order to increase the safety of the dialysis process, the adoption of control measures and monitoring of fungi in hemodialysis fluids is suggested. HIGHLIGHTS Fungi with pathogenic potential in hemodialysis fluids.; Fungi with low susceptibility to antifungals.; Fungi capable of producing biofilm.;